Difficulties of Future Physical Education Teacher for Elementary School in Attending Synchronous Online Learning during Covid-19 Pandemic - Putri, Wulandari (Universitas Pendidikan Indonesia, 2021)
Covid-19 pandemic, started from the beginning of 2020, has changed the learning process in all levels of education in Indonesia. One of the changes is the shift from face-to-face learning into online learning. This research was aimed at finding out the difficulties faced by Physical Education students in joining a synchronous online learning during the pandemic. The study was a mixed-method study with an exploratory approach. The instrument used in the study was a questionnaire containing close-ended and open-ended questions distributed through a Google Form. The link was shared through WhatsApp. The study involved 118 Physical Education students as participants. The result of the study showed that there were four major obstacles faced by the students in attending a synchronous online learning, including technical problems, internet coverage problems, internet quota problems, and environment problems. In addition, the findings also showed that an effort to facilitate online learning has been given by providing internet quota for most of the students. However, it was not sufficient to support a number of synchronous online learnings. The study concludes that those problems became a barrier for students to comprehend the materials optimally and to communicate interactively during the lesson. It is suggested that, to gain an optimal outcome of the synchronous online learning, the betterment and support regarding the technical aspect should be given, such as the development of internet service coverage and internet quota provision.